2003
DOI: 10.1103/physrevb.68.184510
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pauli paramagnetism on the superconducting vortex phase diagram in strong fields

Abstract: The Ginzburg-Landau (GL) functional and the resultant phase diagram of quasi two-dimensional superconductors in strong fields perpendicular to the layers, where the Pauli paramagnetic depairing is not negligible, are examined in details by assuming the weak coupling BCS model with a d x 2 −y 2 -like pairing. It is found that the temperature at which the mean field (MF) transition at Hc2 changes into a discontinuous one lies much above another temperature at which a line HFFLO(T ) of transition to a helical FFL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
268
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(286 citation statements)
references
References 38 publications
14
268
4
Order By: Relevance
“…32,45 The interplay between Pauli paramagnetism and the vortex phase of d-wave superconductors has also been studied in Refs. (36,46).…”
Section: Introductionmentioning
confidence: 99%
“…32,45 The interplay between Pauli paramagnetism and the vortex phase of d-wave superconductors has also been studied in Refs. (36,46).…”
Section: Introductionmentioning
confidence: 99%
“…In the FFLO state, pair-breaking due to the Pauli paramagnetic effect is reduced by the formation of a new pairing state (k↑, −k + q↓) with |q| ∼ 2µ B H/ v F (v F is the Fermi velocity) between the Zeeman split parts of the Fermi surface, instead of (k↑, −k↓)-pairing in ordinary BCS superconductors. A fascinating aspect of the FFLO state is that an inhomogeneous superconducting phase with a spatially oscillating order parameter ∆(r)= ∆ 0 cos(q·r) and spin polarization shows up in the vicinity of the upper critical field H c2 [1,2,3,4,5,6,7,8,9,10,11]. It has been shown that in the presence of a substantial orbital effect, 2D planar nodes appear periodically perpendicular to the Abrikosov vortex lattice.…”
mentioning
confidence: 99%
“…It has been shown that in the presence of a substantial orbital effect, 2D planar nodes appear periodically perpendicular to the Abrikosov vortex lattice. [7,8,9,10,11] Despite the straightforward nature of the theoretical prediction, actual observations of the FFLO state have turned out to be extremely difficult. In fact, no solid evidence, which is universally accepted as proof of the FFLO state, has turned up in any superconductors thus far.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by the recent revival of spatially modulated superconducting (SC) states induced by paramagnetic pair breaking (PPB) [1][2][3][4], noncentrosymmetric superconductors [5] in nonzero magnetic fields have been studied in recent years as a novel type of system with a peculiar modulated SC state. In noncentrosymmetric superconductors, the lack of spatial inversion symmetry results in a splitting of the original Fermi surface into two sheets and makes effects of PPB anisotropic.…”
Section: Introductionmentioning
confidence: 99%